2022
DOI: 10.1039/d1ce01547h
|View full text |Cite
|
Sign up to set email alerts
|

Tremendous boost in the photocatalytic properties of g-C3N4: regulation from polymerization kinetics to crystal structure engineering

Abstract: Graphite carbon nitride (g-C3N4) has become research hotspot owing to its special electronic structure and excellent chemical stability. Although g-C3N4 has made great progress in the field of photocatalysis, its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…[3][4][5] During thermal condensation, the self-generated NH 3 atmosphere will serve as a key kinetic factor to affect the subsequent deamination polymerization. 32,33 We have demonstrated that the prepared g-CN samples exhibit remarkably different photocatalytic activities even under nearly identical synthesis conditions. Although the bulk crystallinity and chemical structures of the samples revealed by XRD and FTIR are very similar (Fig.…”
Section: Synthesis-structure-property Relationshipmentioning
confidence: 94%
See 2 more Smart Citations
“…[3][4][5] During thermal condensation, the self-generated NH 3 atmosphere will serve as a key kinetic factor to affect the subsequent deamination polymerization. 32,33 We have demonstrated that the prepared g-CN samples exhibit remarkably different photocatalytic activities even under nearly identical synthesis conditions. Although the bulk crystallinity and chemical structures of the samples revealed by XRD and FTIR are very similar (Fig.…”
Section: Synthesis-structure-property Relationshipmentioning
confidence: 94%
“…The thermal condensation from melamine to g-CN is deamination polymerization, and the released NH 3 will generate a partial pressure in the reactor, kinetically suppressing the subsequent polymerization process. [32][33][34] The generated NH 3 partial pressure could establish a dynamic equilibrium due to its relatively slow diffusion in static air, retarding the polymerization and concurrently facilitating the decomposition of the primary C-N-H condensates, whereas in flowing air the released NH 3 will be continuously taken away, and thus the following deamination polymerization could occur more sufficiently; meanwhile, the decomposition process would be correspondingly suppressed. As a result, the synthesized CNair possesses a lower production yield as well as a larger SSA than that of CN-air-flow.…”
Section: Experimental Design and Appearance Features Of The Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] However, conventional photocatalysts suffer from a narrow photoresponse range, extremely easy complexation of photogenerated electron-hole pairs, and limited active sites for photocatalytic reactions. [12][13][14] Therefore, the development of efficient and stable photocatalysts to eliminate organic pollution has become an important issue in environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline carbon nitride materials (CNs), such as poly­(heptazine imides) (PHI) and poly­(triazine imide) (PTI), have emerged as highly active photocatalysts for various reactions, including water splitting, CO 2 reduction, hydrogen peroxide synthesis, and organic transformation reactions. Their high activity compared to that of traditional CNs , is due to better light-harvesting properties, high specific surface area, suppressed recombination under illumination, and better charge mobility. , The synthesis of CNs with high crystallinity is typically achieved using molten salts as the reaction medium . The final composition and structure are usually determined by how the salt ions are stabilized at the high temperatures where the CN formation reaction takes place.…”
Section: Introductionmentioning
confidence: 99%